Non-Penal Efforts to Prevent Narcotics Crimes to Realize the Solok Clean Drugs (Sonar) Program by The Solok Regency National Narcotics Agency - Saifuddin Anshori; Fitriati (Master of Law Program, Ekasakti University, 2023)
The National Narcotics Agency of Solok Regency made non-penal efforts with the Solok Clean Drugs Program (Sonar) which was stated based on the Decree of the Head of the National Narcotics Agency of Solok Regency Number: KEP/KPTS/01/BNNK Solok-SLK/2021. Until 2022 in Solok Regency, there are only 5 nagari out of 74 nagari that have declared themselves as drug-clean nagari. This program aims to overcome crime through non-penal efforts that focus on prevention efforts by involving villages / nagari, to realize the Sonar Program is by implementing Three Pillars, namely prevention and community empowerment, eradication, and rehabilitation. In the implementation of these three pillars, what is put forward is prevention and community empowerment and rehabilitation by carrying out activities in the form of mentoring, advocacy, information dissemination in order to strengthen the development of anti-drug insight; Anti-Narcotics Community Empowerment, Community-Based Interventions, Technical Guidance for Anti-Narcotics Enthusiasts, and Rehabilitation Clinic Services However, its implementation in the field has encountered obstacles.